PENGARUH IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SMK PGRI WONOASRI - Satrijo Budi Wibowo (Jurnal Pendidikan, 2012)
One out of the most critical educational issues in Indonesia is the questionable quality of education at every level and unit. Managerial problems of education have already been existing since Orde Baru, when Integrated Development School (IDS) was firstly inacted being followed by Schoool-Based Management (SBM). Both are the same except the operating system; IDS tends to be centralized while SBM tends to be  decentralized. Both work for the development of educational quality, but IDS, is regarded less accomodative with its old-fashioned paradigm, in line with inaction of Regulation No 22, year 1999. The regulation brings about conse-quences of regional authorities to manage regional development, including educational sector. SBM has been proposed to offer school autonomy in establishing school policies in accomodating the development in quality, effeciency and distribution by the optimal colaboration of schools, society and goverment. This reserach is served to identify the significance of SBM against the quality improvement of education at SMK PGRI Wonoasri.The research is conducted at SMK PGRI Wonoasri, under the total sampling technique, coping with all of 63 teachers. The data for analysis are promary data which are taken by direct observation with questionaires, and interviewing techniques. The analysis is carried out by simple linear regression technique and product moment correlation technique of Statistical Product and Service Solutions (SPSS) for windows, version 17.0.The results of computation shows that product t is 8.249, which is significant in comparison with the table t of 2.000 under the significance level pf 5%. The regression computation result in score of 0.726 at the significance of 0.000. based on the computations, the implementation of SBM influence significantly on the educational quality development at SMK PGRI Wonoasri.